The talk show and documentary format in the story of sexist violence. The cases of Ana Orantes and Rocío Carrasco - Bernal Triviño, Ana (Comunicación y Género [Communication and Gender], 2023)
The media, according to Spanish law 1/2004, have the recommendation to raise awareness of gender violence. Among the various journalistic genres, the news and the report are the most consolidated options, but television, as one of the most watched options among the population, allows the development of other formats for the story of far-reaching gender violence. Through two media cases, Ana Orantes and Rocío Carrasco, comparisons and differences between the talk show and serial documentary formats are specified to detect their differences, similarities and social impact on the coverage of gender violence. The research concludes that these television formats were valid for making a more personal account of this violence, delving into experiences and having a greater social impact, to the point of being a starting point for adopting political measures.
Keywords: gender violence; talk show; docuserie; Ana Orantes; Rocío Carrasco